(untitled) (Sudurpaschim Spectrum, 2024)
Non-timber forest products (NTFPs) are crucial for the economic stability and daily needs of rural communities in Nepal, offering resources like food, medicine, fiber, and construction materials. In the Dadeldhura district, NTFPs are integral to local livelihoods and traditional health practices. However, their sustainability is threatened by overharvesting and rising demand, highlighting the need for effective conservation strategies. This study examines the role of NTFPs in Nepal, utilizing a mixed-methods approach that includes structured household surveys and both qualitative and quantitative data analysis. The study reveals that 40.5% of the community earns between 25,000 to 50,000 annually, reflecting economic challenges and reliance on NTFPs. Additionally, 76.13% of collected NTFPs are primarily used for trade, underscoring their significant economic role. The findings suggest a need for improved market access, processing facilities, and community-based management to enhance the sustainability and economic benefits of NTFPs. This research offers valuable insights for local authorities, emphasizing the importance of targeted management efforts to ensure the continued availability and economic potential of NTFPs, ultimately benefiting the livelihoods of Nepal’s rural populations.